Creative Thinking Skills Through Project-Based Learning (PjBL)-STEM - Rahayu, Ika Putri; Wulandari, Fitria (Jurnal Pijar Mipa, 2025)
Creative thinking skills are important for students in generating ideas, learning, and ease of processing information. The PjBL-STEM model, in line with 21st century learning, empowers students to develop talents and abilities. This study aims to determine the improvement of students' creative thinking skills and the effect of the PjBL-STEM model on students' creative thinking skills. This type of research uses a quantitative approach with a pre-experiment method with One Group Pretest-Posttest Design. Sampling was taken using saturated sampling technique, namely all fourth-grade students of UPT SDN 173 Gresik, totalling 22 students. Data collection techniques involve giving tests with research instruments in the form of creative thinking skills questions that have been validated and are reliable. Data analysis used the N-Gain Test to determine the increase in creative thinking ability indicators after implementing the PjBL-STEM model and paired sample T-test to determine the effect of the PjBL-STEM model on students' creative thinking ability with a significance level of 0.05. The results showed that the average N-Gain value was 0.77 which means that there was an increase in students' creative thinking skills with a high category and the results of the paired sample T-test analysis obtained a significant value of 0.000> 0.05 which means that there is a statistically significant difference between the creative thinking skills of students before and after the application of the PjBL-STEM model, so it can be concluded that the PjBL-STEM model is effective for increasing the influence of students' creative thinking skills. In the broader world of education, applying the PjBL-STEM model can empower students to develop talents and abilities holistically per the demands of the 21st-century curriculum, while improving STEM literacy, collaboration skills, and learning independence. Therefore, integrating the PjBL-STEM model in the current curriculum can strengthen meaningful, relevant, and contextualized learning, and prepare students to face real-world challenges with better creative thinking skills.